Mentoring strategy as catalyst for achieving survival of transport companies in south-east Nigeria - Nwatoka, Kenechukwu T.; Olamide, Ohunyeye F.; Nkiru, Nwakoby P.; N. Ike, Mba Sr (Opción, 2020)
Succession planning is an amalgamated strategic management component put in place to ensure the continued survivability of the entire organization, division, department, or work group by making insightful provisions for the development, advancement, replacement and strategic application of key people for successful trans-generational transition. The study sought to ascertain how mentoring strategy could influence organizational sustainability in selected motor transport companies in south East Nigeria. The data collected through the closed ended questionnaires were tested with linear regression at 0.05 significance level. In conclusion, an effective employee mentoring process is the catalyst to ensure that the organization has the potential successors with the right skills and attributes it requires to meet future business needs.